Semantic Analysis of “Heart“ Component Phrases and Alternative Translations in English Which Were Used in the Story “Naughty Boy” by Ghafur Ghulam (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article will conduct a semantic analysis and analysis of the semantic features of the “heart” component phrases used in the short story “Naughty boy” by Ghafur Ghulam. In particular, information is also provided about the monosemantic and polysemantic properties of phrases, types according to the relationship of form and meaning. Examples of English-translated alternatives to the “heart” component phrases used in the narrative are also given, with reference to translation methods.